Bullying and Attitudes Toward Masculinity in Croatian Schools: Behavioral and Emotional Characteristics of Students Who Bully Others - Gereš, Natko (Journal of interpersonal violence, 2021)
Prevention of bullying is paramount to creating a positive and welcoming school environment. This study compared the following characteristics reported by students who had perpetrated bullying in Croatian schools and those who did not: gender, type of school, family wealth, negative emotionality, behaviors that may compromise health, and endorsement of traditional masculinity. Within the framework of the “Croatian Adolescent Masculinity Study,” second and third grade students of secondary schools (equivalent to tenth and eleventh grade in the United States) in the city of Zagreb (N = 4,072) completed a cross-sectional, paper-and-pencil survey. Descriptive and logistic regression analyses were conducted separately for males and females to identify constructs associated with bullying perpetration. More males (12.7%) than females (5.8%) perpetrated bullying. Compared to students who did not report bullying others, significantly more students, who perpetrated bullying reported feeling sad or hopeless, having suicidal ideation, carrying a weapon, missing school because of feeling unsafe, drinking alcohol, getting inebriated, being victims of bullying, and endorsing traditional masculinity norms. The proportion of males reporting bullying others did not vary by type of school; females were more likely to perpetrate bullying in predominantly male and mixed-gender vocational schools. Bullying prevention interventions should address the complexity of problems associated with bullying others. Students who reported bullying others were more likely to participate in other harmful behaviors and have emotional problems. Endorsement of traditional masculinity norms should be further researched in other cultures and included in investigations of bullying perpetration, given its association with increased bullying among male and female students.